Improved high-resolution pediatric vascular cardiovascular magnetic resonance with gadofosveset-enhanced 3D respiratory navigated, inversion recovery prepared gradient echo readout imaging compared to 3D balanced steady-state free precession readout imaging - Tandon, Animesh (J Cardiovasc Magn Reson, 2016)
BACKGROUND: Improved delineation of vascular structures is a common indication for cardiovascular magnetic resonance (CMR) in children and requires high spatial resolution. Currently, pre-contrast 3D, respiratory navigated, T2-prepared, fat saturated imaging with a bSSFP readout (3D bSSFP) is commonly used; however, these images can be limited by blood pool inhomogeneity and exaggeration of metal artifact. We compared image quality of pediatric vasculature obtained using standard 3D bSSFP to 3D, respiratory navigated, inversion recovery prepared imaging with a gradient echo readout (3D IR GRE) performed after administration of gadofosveset trisodium (GT), a blood pool contrast agent. METHODS: For both sequences, VCG triggering was used with acquisition during a quiescent period of the cardiac cycle. 3D bSSFP imaging was performed pre-contrast, and 3D IR GRE imaging was performed 5 min after GT administration. We devised a vascular imaging quality score (VIQS) with subscores for coronary arteries, pulmonary arteries and veins, blood pool homogeneity, and metal artifact. Scoring was performed on axial reconstructions of isotropic datasets by two independent readers and differences were adjudicated. Signal- and contrast-to-noise (SNR and CNR) calculations were performed on each dataset. RESULTS: Thirty-five patients had both 3D bSSFP and 3D IR GRE imaging performed. 3D IR GRE imaging showed improved overall vascular imaging compared to 3D bSSFP when comparing all-patient VIQS scores (n = 35, median 14 (IQR 11–15), vs 6 (4–10), p < 0.0001), and when analyzing the subset of patients with intrathoracic metal (n = 17, 16 (14–17) vs. 5 (2–9), p < 0.0001). 3D IR GRE showed significantly improved VIQS subscores for imaging the RCA, pulmonary arteries, pulmonary veins, and blood pool homogeneity. In addition, 3D IR GRE imaging showed reduced variability in both all-patient and metal VIQS scores compared to 3D bSSFP (p < 0.05). SNR and CNR were higher with 3D IR GRE in the left ventricle and left atrium, but not the pulmonary arteries. CONCLUSIONS: Respiratory navigated 3D IR GRE imaging after GT administration provides improved vascular CMR in pediatric patients compared to pre-contrast 3D bSSFP imaging, as well as improved imaging in patients with intrathoracic metal. It is an excellent alternative in this challenging patient population when high spatial resolution vascular imaging is needed.